EFEKTIVITAS PENGELOLAAN APLIKASI VISITING JOGJA DALAM PENGEMBANGAN PARIWISATA DI DAERAH ISTIMEWA YOGYAKARTA - Radityo Prayoga, Gusti; Subowo, Ari; Afrizal, Teuku (Journal of Public Policy and Management Review, 2024)
Presidential Instruction Number 3 of 2003 requires the Indonesian government to implement E- Government as an effort to increase efficiency and transparency in providing public services. One form of effort to implement E-Government through the tourism sector is by creating digital-based media that facilitates tourists and tourism destination managers. This digital tourism media is very helpful for the tourism sector, especially during the Covid-19 pandemic and the new normal period. D.I Yogyakarta is one of the provinces that uses digital media as a center for DIY tourism information, the application is called Visiting Jogja. However, in its implementation, there are still several problems in the visiting jogja application. The main complaints of users are problems during registration and applications that cannot be used. The purpose of this study is to analyze the effectiveness of the management of the visiting jogja application in developing tourism in DIY using the effectiveness theory by Siagian. This study uses a descriptive qualitative research method with data collection techniques through observation, interviews, and documentation. The results of the study show that the effectiveness of the management of the visiting jogja application is good, but there are several dimensions that need to be improved. The dimensions include the dimensions of facilities and infrastructure, where the computer equipment used is not too sophisticated and seems outdated and the information service facilities are inadequate. The second dimension is the time dimension, where the target achievement time is not determined.